2014
DOI: 10.1093/treephys/tpu002
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal carbohydrate dynamics and growth in Douglas-fir trees experiencing chronic, fungal-mediated reduction in functional leaf area

Abstract: Stored non-structural carbohydrates (NSCs) could play an important role in tree survival in the face of a changing climate and associated stress-related mortality. We explored the effects of the stomata-blocking and defoliating fungal disease called Swiss needle cast on Douglas-fir carbohydrate reserves and growth to evaluate the extent to which NSCs can be mobilized under natural conditions of low water stress and restricted carbon supply in relation to potential demands for growth. We analyzed the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 43 publications
2
27
1
Order By: Relevance
“…If this pattern would only show in control trees, one could argue that water deficit will limit cell division and enlargement (Hsiao & Acevedo 1974), NSC mobilization and transport in the phloem (Sevanto 2014), but the same relationship between %NSC, TNC and ring width showed in the irrigated trees for which we can reasonably exclude any significant water limitation. Our results thus suggest an active control of carbon storage as opposed to a passive overflow storage of carbon not used for growth (Sala, Woodruff & Meinzer 2012;Saffell et al 2014).…”
Section: R a D I A L N S C S T O R A G E P A T T E R N S I N S A P W mentioning
confidence: 76%
See 1 more Smart Citation
“…If this pattern would only show in control trees, one could argue that water deficit will limit cell division and enlargement (Hsiao & Acevedo 1974), NSC mobilization and transport in the phloem (Sevanto 2014), but the same relationship between %NSC, TNC and ring width showed in the irrigated trees for which we can reasonably exclude any significant water limitation. Our results thus suggest an active control of carbon storage as opposed to a passive overflow storage of carbon not used for growth (Sala, Woodruff & Meinzer 2012;Saffell et al 2014).…”
Section: R a D I A L N S C S T O R A G E P A T T E R N S I N S A P W mentioning
confidence: 76%
“…Our results thus suggest an active control of carbon storage as opposed to a passive overflow storage of carbon not used for growth (Sala, Woodruff & Meinzer ; Saffell et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…; Hartmann, Ziegler & Trumbore ), while above‐ground tissues use sugars for osmoregulation or to rebuild the crown (Saffell et al . ). Overall, our findings confirm that the sapwood concentrations of SS reflect crown defoliation in the two pine species whereas needle chemical variables (NSC, N, δ 13 C) do not.…”
Section: Discussionmentioning
confidence: 97%
“…There is evidence that even under severe stress conditions, C reserves are never fully depleted (Gruber et al 2012;Hartmann et al 2013;Klein et al 2014) and that reserve storage may, in certain cases, be favored at the expense of growth (Wiley et al 2013;Saffell et al 2014). Recent studies have demonstrated that, within a given growing season, the formation of C reserves occurs earlier in mature trees compared to young trees in experiments conducted under the same pedoclimatic conditions and leaf phenology (Gilson et al 2014).…”
Section: The Phenology Of Carbon and Nitrogen Reservesmentioning
confidence: 99%